2019
DOI: 10.1177/0954407019864210
|View full text |Cite
|
Sign up to set email alerts
|

Design of a frictional–electromagnetic compound disk brake for automotives

Abstract: According to the disadvantages of serious wear and heat fade of friction pad in frequent and high speed braking of friction brakes, and the insufficient power of electromagnetic brakes in low speed braking, a novel frictional-electromagnetic compound disk brake which combines both of these two brake principles is proposed for automotives in this paper. The excitation coils are designed based on the Zhang Yicheng theory model, and the compound brake prototype is manufactured based on the self-made magnetic brak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…He et al [13] utilized the power bond diagram method to establish a non-linear coupling mathematical model of the integrated system of electromagnetic brake and friction brake, and through experiments to validate the accuracy of the nonlinear coupling mathematical model, provides theoretical guidance for the design of electromagnetic friction brakes. Huang et al [14] through the friction-braking compound experiment verified that friction braking torque accounts for more than 90% of the friction braking torque in the electromagnetic friction braking device. Choi et al [15] utilized the finite element method (FEM) to analyze the frictional heat contact problem during the braking process of disc brakes, and obtained the temperature distribution of the friction disc surface under different braking loads.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [13] utilized the power bond diagram method to establish a non-linear coupling mathematical model of the integrated system of electromagnetic brake and friction brake, and through experiments to validate the accuracy of the nonlinear coupling mathematical model, provides theoretical guidance for the design of electromagnetic friction brakes. Huang et al [14] through the friction-braking compound experiment verified that friction braking torque accounts for more than 90% of the friction braking torque in the electromagnetic friction braking device. Choi et al [15] utilized the finite element method (FEM) to analyze the frictional heat contact problem during the braking process of disc brakes, and obtained the temperature distribution of the friction disc surface under different braking loads.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al demonstrated that EDCs may also be utilized in automotive powertrains, where they can be used as a flexible link between the wheel hub and motor for high levels of comfort and smooth power transmission [8,9]. A fractional electromagnetic compound disk brake is another application of electromagnetic actuators, and it demonstrates favorable braking performance [10]. Medei [11] studied the implementation of a passive decoupler to isolate vibrations exchanged between the crankshaft and the FEAD.…”
Section: Introductionmentioning
confidence: 99%
“…In [2,3] and concepts are presented in which the eddy 40 current brake and the friction brake are operated locally separately. In other concepts [4,5], 41 additional excitation poles are positioned on the brake disk to generate eddy currents and 42 thus a wear-free portion of the braking torque. All these concepts generate the frictional 43 torque via a classic brake caliper.…”
Section: Introductionmentioning
confidence: 99%